Analyzing Medication Adherence Patterns Among Type 2 Diabetes Patients in Thi-Qar, Iraq: A Cross-Sectional Study - Adel Gassab Mohammed; Nassar Taha Yaseen; Dheyaa K. AlWaeli (Journal of Diabetes Research)
This research investigates the adherence levels to diabetes treatment among patients and explores the factors influencing adherence, glycemic control, and the occurrence of diabetes-related complications. A cross-sectional study involving 296 diabetes patients was conducted to evaluate their demographic and clinical profiles, treatment strategies, and adherence levels using the eight-item Morisky Medication Adherence Scale (MMAS-8). Statistical analyses identified variables affecting adherence and their relationships with glycemic control and complications. The study population comprised 56% men, with an average age of 49.4 years. Obesity was observed in 24.3% of participants, while the median disease duration was 5 years. The average HbA1c level was 8.4%. Microvascular complications were present in 48.6% of patients, and 18.2% experienced macrovascular complications. Most patients were prescribed oral antidiabetic medications (OAD), with 25% receiving insulin therapy. Adherence rates were suboptimal, with only 3.4% achieving good adherence, 30.4% moderate adherence, and 66.2% poor adherence. Men had higher rates of poor adherence compared to women (72.3% vs. 58.5%). Interestingly, adherence was better in patients with a longer disease duration and a higher body mass index (BMI). The study further examined adherence’s impact on glycemic outcomes, finding that poor adherence strongly correlated with elevated HbA1c levels. Among individuals with HbA1c≥7%, 70.5% exhibited poor adherence, whereas 40% of patients with good adherence still had suboptimal glycemic control. Conversely, among those with HbA1c<7%, 24.5% demonstrated poor adherence compared to 40% with good adherence. Random blood sugar (RBS) levels were significantly higher in poorly adherent patients (237 mg/dL) versus those with good adherence (141 mg/dL). Although adherence was not statistically linked to complication prevalence, patients with reported adherence challenges were more prone to both microvascular and macrovascular complications. Different treatment regimens were also analyzed, revealing that sulfonylureas (SUs) were associated with poor adherence (85%), while sodium–glucose cotransporter 2 inhibitors (SGLT2i) showed better adherence rates (16.7%). Missed doses were strongly linked to poor glycemic outcomes but had a lesser impact on complication development. These findings underscore the need for individualized strategies to enhance adherence and optimize glycemic control, ultimately reducing diabetes-related complications.